2018
DOI: 10.1111/lam.13003
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state fermentation by Trichoderma viride for enhancing phenolic content, antioxidant and antimicrobial activities in ginger

Abstract: This is the first report to investigate the optimal physiological conditions of solid-state fermentation (SSF) of ginger by Trichoderma viride for enhancing its phenolic content and antioxidant capacity. In addition, the phenolic compounds of fermented ginger could be potentially used as a dietary adjunct and an antibacterial agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…Temperature also plays a critical role in microbial growth and production of cell wall degradation enzymes. Similar to our finding, at 30°C of SSF, the polyphenols content of fermented bush tea and ginger significantly increased, whereas the lowest levels of polyphenols were detected at 20 and 40°C (Hlahla et al ; Saleh et al ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Temperature also plays a critical role in microbial growth and production of cell wall degradation enzymes. Similar to our finding, at 30°C of SSF, the polyphenols content of fermented bush tea and ginger significantly increased, whereas the lowest levels of polyphenols were detected at 20 and 40°C (Hlahla et al ; Saleh et al ).…”
Section: Discussionsupporting
confidence: 91%
“…The response surface methodology reported that maximum production of phenolic content and carbohydrate‐cleaving enzymes from GCS by SSF was recorded at 30°C, pH 7·0, 30% moisture and 5‐day incubation. Similarly, the phenolic content and antioxidant capacity of fermented maize were highly increased on day 5 of incubation (Salar et al ), whereas the maximum production of phenolic content from fermented ginger was detected on day 7 of incubation (Saleh et al ). Among the selected SSF parameters, the moisture content plays a significant role during SSF process as the micro‐organisms have different moisture requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant‐derived antimicrobials have been researched and consumed frequently over the past decade to improve quality of health and provide ethnopharmacological remedies (Nittayananta, Limsuwan, Srichana, Sae‐Wong, & Amnuaikit, ; Tang, Prodhan, Biswas, Le, & Sekaran, ). Flavonoid, which is the most abundant type of polyphenolic compound found in plant materials, was studied to increase in concentration and antibacterial activity using acid hydrolysis (Min, Kim, Lee, Kim, & Paik, ), fermentation (Saleh et al, ), and silver nanoparticles (Rashid et al, ). In this study, fermentation was used to increase the antimicrobial activity of I. britannica extract.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, phenolic compound compo- 2018). Flavonoid, which is the most abundant type of polyphenolic compound found in plant materials, was studied to increase in concentration and antibacterial activity using acid hydrolysis (Min, Kim, Lee, Kim, & Paik, 2014), fermentation (Saleh et al, 2018), and silver nanoparticles (Rashid et al, 2017). In this study, fermentation was used to increase the antimicrobial activity of I. britannica extract.…”
Section: Discussionmentioning
confidence: 99%